PENGARUH KECERDASAN EMOSIONAL, MOTIVASI EKSTRINSIK, DAN DUKUNGAN ORGANISASIONAL TERHADAP KINERJA KARYAWAN PADA PERUMDA TIRTA AMERTHA BUANA KABUPATEN TABANAN - Ni Made Rani Untari; I Wayan Sujana; Ni Nyoman Ari Novarini (EMAS, 2021)
Performance is the work result in quality and quantity achieved by an employee in carrying out his duties according to the responsibilities assigned to him. The purpose of this study was to determine the effect of emotional intelligence, extrinsic motivation, and organizational support on employee performance at Perumda Tirta Amertha Buana, Tabanan Regency. This research was conducted at Perumda Tirta Amertha Buana Tabanan Regency using 45 employees. The technique of determining the sample in this study is the census method. Data collection was carried out through interviews and questionnaires. The data analysis technique used in this study is multiple linear regression analysis processed using SPSS software. Based on the results of the analysis, this study shows that emotional intelligence has a positive and significant effect on employee performance. Extrinsic motivation has a positive and significant effect on employee performance. Organizational support has a positive and significant effect on employee performance. Emotional intelligence, extrinsic motivation, and organizational support simultaneously influence employee performance